The Human Endolymphatic Sac and Inner Ear Immunity: Macrophage Interaction and Molecular Expression - Kämpfe Nordström, Charlotta; Danckwardt-Lillieström, Niklas; Laurell, Göran; Liu, Wei; Rask-Andersen, Helge (Frontiers in Immunology, 2019)
Background: The endolymphatic sac (ES) is endowed with a multitude of white blood cells that may trap and process antigens that reach the inner ear from nearby infection-prone areas, it thus serves as an immunologic defense organ. The human ES, and unexpectedly the rest of the inner ear, has been recently shown to contain numerous resident macrophages. In this paper, we describe ES macrophages using super-resolution structured fluorescence microscopy (SR-SIM) and speculate on these macrophages' roles in human inner ear defense. Material and Methods: After ethical permission was obtained, human vestibular aqueducts were collected during trans-labyrinthine surgery for acoustic neuroma removal. Tissues were placed in fixative before being decalcified, rapidly frozen, and cryostat sectioned. Antibodies against IBA1, cytokine fractalkine (CX3CL1), toll-like receptor 4 (TLR4), cluster of differentiation (CD)68, CD11b, CD4, CD8, and the major histocompatibility complex type II (MHCII) were used for immunohistochemistry. Results: A large number of IBA1-positive cells with different morphologies were found to reside in the ES; the cells populated surrounding connective tissue and the epithelium. Macrophages interacted with other cells, showed migrant behavior, and expressed immune cell markers, all of which suggest their active role in the innate and adaptive inner ear defense and tolerance. Discussion: High-resolution immunohistochemistry shows that antigens reaching the ear may be trapped and processed by an immune cell machinery located in the ES. Thereby inflammatory activity may be evaded near the vulnerable inner ear sensory structures. We speculate on the immune defensive link between the ES and the rest of the inner ear.